Anti-Salmonella Defence and Intestinal Homeostatic Maintenance In Vitro of a Consortium Containing Limosilactobacillus fermentum 3872 and Ligilactobacillus salivarius 7247 Strains in Human, Porcine, and Chicken Enterocytes - Vyacheslav M. Abramov; Igor V. Kosarev; Andrey V. Machulin; Evgenia I. Deryusheva; Tatiana V. Priputnevich; Alexander N. Panin; Irina O. Chikileva; Tatiana N. Abashina; Ashot M. Manoyan; Anna A. Akhmetzyanova; Dmitriy A. Blumenkrants; Olga E. Ivanova; et al. (MDPI AG, 2023)
Limosilactobacillus fermentum strain 3872 (LF3872) was originally isolated from the breast milk of a healthy woman during lactation and the breastfeeding of a child. Ligilactobacillus salivarius strain 7247 (LS7247) was isolated at the same time from the intestines and reproductive system of a healthy woman. The genomes of these strains contain genes responsible for the production of peptidoglycan-degrading enzymes and factors that increase the permeability of the outer membrane of Gram-negative pathogens. In this work, the anti-Salmonella and intestinal homeostatic features of the LF3872 and LS7247 consortium were studied. A multi-drug resistant (MDR) strain of Salmonella enteritidis (SE) was used in the experiments. The consortium effectively inhibited the adhesion of SE to intact and activated human, porcine, and chicken enterocytes and reduced invasion. The consortium had a bactericidal effect on SE in 6 h of co-culturing. A gene expression analysis of SE showed that the cell-free supernatant (CFS) of the consortium inhibited the expression of virulence genes critical for the colonization of human and animal enterocytes. The CFS stimulated the production of an intestinal homeostatic factor-intestinal alkaline phosphatase (IAP)-in Caco-2 and HT-29 enterocytes. The consortium decreased the production of pro-inflammatory cytokines IL-8, TNF-α, and IL-1β, and TLR4 mRNA expression in human and animal enterocytes. It stimulated the expression of TLR9 in human and porcine enterocytes and stimulated the expression of TLR21 in chicken enterocytes. The consortium also protected the intestinal barrier functions through the increase of transepithelial electrical resistance (TEER) and the inhibition of paracellular permeability in the monolayers of human and animal enterocytes. The results obtained suggest that a LF3872 and LS7247 consortium can be used as an innovative feed additive to reduce the spread of MDR SE among the population and farm animals.